Acute Effects Using Light-Emitting Diode Therapy (LEDT) for Muscle Function during Isometric Exercise in Asthma Patients: A Pilot Study. (16th January 2019) - Costa, Ivan Peres; Politti, Fabiano; Cahalin, Lawrence P.; Carvalho, Etiene Farah Teixeira de; Costa, Dirceu; Corrêa, João Carlos Ferrari; Vieira, Rodolfo P.; Oliveira-Junior, Manoel Carneiro; De Angelis, Kátia; Stirbulov, Roberto; Dal Corso, Simone; de Carvalho, Paulo de Tarso; et al.
Abstract : The aim of this study was to evaluate the effectiveness of acute application of LEDT in improving peripheral muscle performance during isometric exercise in patients with asthma. Eleven patients, with a mean age 38 ± 10, underwent a single LEDT and sham application in the femoral quadriceps' dominant member (cluster with 50 LED λ = 850 nm, 50 mW, 15 s; 37.5 J), 48 h apart in a randomized crossover design. Before and after LEDT and sham application, the patients were submitted an isometric endurance test (60% of the maximum isometric voluntary contraction), up to the limit of tolerance simultaneous recording of surface electromyography. There were no statistically significant differences between groups at the time of contraction (before 41±14 versus 44±16; after 46±12 versus 45±20 s) during the isometric contraction test and inflammatory markers before and after a single LEDT application. A single application of LEDT in the parameters and dose according to the equipment used in the study were not able to promote differences in the time of contraction and the fatigue response in asthmatic patients. However, the chronic effects of LEDT application for improving muscle performance in these patients are unknown and may present different responses during applications for a long time.